Escolhas temáticas no discurso de guias de turismo e monitores de museus no Brasil e na Espanha - Pereira, Danielle Toledo (2005)
This research, part of the DIRECT Project (LAEL/PUC-SP), aims at analyzing the characteristics of city tour and museum guides in two different sociocultural contexts: Brazil and Spain. In this way, it investigates the cultural context and the situational context of the corpora of this study. The theory focuses on Systemic Functional Grammar (Halliday, 1994). Although this grammar offers various elements that could also reveal characteristics in the discourse of these professionals, Theme was chosen because it makes possible the study of the organization of the message, the point of departure the speaker selects for grounding what he is going to say (Halliday (1994: 34). Besides, it is possible to compare how two different languages and cultures organize their message. This research has three goals: (1) to identify similarities and differences in the discourse of city tour and museum guides; (2) to identify similarities and differences in the discourse of Brazilian and Spanish city tour and museum guides; (3) to establish if there is one or two genres according to the general structure of the discourses and to Thematic options. Thus, this study is composed of 04 corpora: one of visits to two Brazilian museums; one of visits to two Spanish museums; one of two city tours in Brazil; one of two city tours in Spain. The visits were recorded in cassette tapes and transcribed. The theory about genre follows the ideas of Hasan (1989), Swales (1990), Bathia (1993), Fries (1995), Eggins & Martin (1997) and Ramm (2000). The Theme was studied through the ideas of Halliday (1994), Eggins (1994), Berry (1995), Thompson (1996), Barbara & Gouveia (2001) and Gouveia & Barbara (2001). Results show that city tour and museum guides organize their discourse in a very similar way and that there are some idiosyncratic differences, what is expected as the study deals with two sociocultural contexts